Preparing Iraq to Cope with Natural Disasters Due to Climate Change: A Study of National Preparedness to Respond to the Impacts of Natural Disasters such as Floods and Drought. /A Review Article - Ahmed A. Hashim; Omer Abdul Kareem Aswad; Estabraq Mohammed Ati; Naji Ajmi (Peerian Journals Publishing, 2025)
This study aims to gain an insight into Iraq's preparedness to mitigate natural disasters triggered by climate change, specifically drought, floods, and dust storms. It explores the country's climatic issues, assesses the institutional and legislative framework that exists, looks into national disaster reduction plans, and identifies short- and long-term preparedness requirements. The study adopted a descriptive analytical approach based on a review of current literature and international and national reports related to climate change and disaster management in Iraq. It also depended on data and statistics from international organizations such as the World Bank, the United Nations Development Programme, and the United Nations Environment Programme, as well as on current Iraqi academic research. The article concludes that Iraq is faced with complex and interconnected challenges induced by climate change and that its national response is incomplete both in planning and implementation, despite having legislative foundations and early strategies. Institutional coordination weakness, financial and technical capacity weakness, and low awareness at the community level are the most apparent obstacles to formulating an effective and resilient response to disasters.
Keywords: Climate change; disaster management; national preparedness